Malignant ulcer: a great mimicker of gastric plasmablastic lymphoma - Syamim Johan; Allim Khairuddin; Asyraf Mohd Zuki; Wei Woon Teng; Firdaus Hayati; Aung Mra; Nornazirah Azizan (Springer Nature, 2021)
Plasmablastic lymphoma (PBL) is an uncommon human immunodeficiency virus (HIV)-associated lymphoma, with a predilection to develop in the oral cavity. It usually has a plasmablastic morphology with weak or no expression of B cell-associated markers. Among non-HIV patients, it tends to occur in the gastrointestinal (GI) tract, lymph nodes, and skin. We experience a 74-year-old male who presented with abdominal discomfort, altered bowel habit, loss of weight, and loss of appetite with a palpable abdominal mass. Upper endoscopy revealed multiple dish-like and raised nodular mass with a central ulcer in the stomach and duodenum. The histology was consistent with high-grade lymphoma of the plasmablastic type. The immunohistochemistry was positive for plasma cells marker of CD38 and CD138, but negative for the lymphocytic marker of CD45, as well as mature T and B cell marker of CD3 and CD20. Unfortunately, the patient succumbed due to sepsis without completion of his investigations and treatments.